Combined effect of silver ion and pyrite on AMD formation generated by chalcopyrite bio-dissolution. (September 2021) - Liao, Rui; Yang, Baojun; Huang, Xiaotao; Hong, Maoxing; Yu, Shichao; Liu, Shitong; Wang, Jun; Qiu, Guanzhou
Abstract: Chalcopyrite is a crucial contributor causing acid mine drainage (AMD). Silver and pyrite are commonly co-existed with chalcopyrite, and can significantly affect the copper release from chalcopyrite bio-dissolution process. However, the combined effect of them on chalcopyrite bio-dissolution has not been illustrated up to now. To fill this knowledge gap, the combined effect of silver and pyrite on chalcopyrite dissolution with Acidithiobacillus ferrooxidans was investigated in this study. The copper extraction reached the maximum value (62.3 ± 0.1%) with the presence of silver and pyrite, which was 43.8 ± 0.1% higher than the control group (without addition). This suggested more copper ions and acids were released under this circumstance. According to bio-dissolution results, SEM, XRD and XPS analyses, the promotion effect of silver and pyrite on chalcopyrite bio-dissolution was mainly attributed to the increase of ferric ions in solution and the reduction of passivation layer (Sn 2− /S 0 ) on chalcopyrite surface. The investigation into the bio-dissolution of chalcopyrite is important for controlling the generation of copper ions and acids. Silver or pyrite bearing chalcopyrite should be carefully treated to avoid the pollution of heavy metal copper and acid in the mining environment. Graphical abstract: Silver could reduce the formation of passivation layer, and pyrite could produce lots of ferric ions and accelerate the regeneration of silver ion, thus enhancing chalcopyrite bio-dissolution and releasing more copper ions and acids into the environment. Image 1 Highlights: Silver or pyrite bearing chalcopyrite should be carefully treated to avoid AMD formation in mining site. Silver and pyrite could enhance chalcopyrite bio-dissolution. Silver could reduce the formation of passivation layer (Sn 2− /S 0 ). Pyrite could produce lots of ferric ions and accelerate chalcopyrite bio-dissolution and the regeneration of silver ion. The jarosite formed in silver and/or pyrite added chalcopyrite system would not hinder the dissolution process.